2021
DOI: 10.1002/adsc.202001590
|View full text |Cite
|
Sign up to set email alerts
|

Aromatic C−H Hydroxylation Reactions with Hydrogen Peroxide Catalyzed by Bulky Manganese Complexes

Abstract: The oxidation of aromatic substrates to phenols with H2O2 as a benign oxidant remains an ongoing challenge in synthetic chemistry. Herein, we successfully achieved to catalyze aromatic C−H bond oxidations using a series of biologically inspired manganese catalysts in fluorinated alcohol solvents. While introduction of bulky substituents into the ligand structure of the catalyst favors aromatic C−H oxidations in alkylbenzenes, oxidation occurs at the benzylic position with ligands bearing electron‐rich substitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(54 citation statements)
references
References 109 publications
2
50
0
Order By: Relevance
“…This finding agrees with our previous study on the oxidation of aromatic substrates catalyzed by bioinspired manganese complexes, where electron-rich Mn complexes show the formation of benzylic alcohols as the main oxidized product, whereas aromatic oxidation toward phenols occurs to a lower extent. 73 Under these conditions, complexes (S,S)-1 and 2 generate the alcohol product 6a in 34 to 35% yield, together with the ketone product 6b in 4 to 5% yield and trace amounts of the aromatic oxidation products. For both complexes the (S)-alcohol product formed in 32 and 33% ee, respectively, showing that a change in the amine backbone does not induce a significant change in enantioselectivity.…”
Section: Pyrrolidine Vs Dimethylamino: Amine-substituted Pyridines In Mncatalyzed Benzylic Oxidationmentioning
confidence: 98%
See 1 more Smart Citation
“…This finding agrees with our previous study on the oxidation of aromatic substrates catalyzed by bioinspired manganese complexes, where electron-rich Mn complexes show the formation of benzylic alcohols as the main oxidized product, whereas aromatic oxidation toward phenols occurs to a lower extent. 73 Under these conditions, complexes (S,S)-1 and 2 generate the alcohol product 6a in 34 to 35% yield, together with the ketone product 6b in 4 to 5% yield and trace amounts of the aromatic oxidation products. For both complexes the (S)-alcohol product formed in 32 and 33% ee, respectively, showing that a change in the amine backbone does not induce a significant change in enantioselectivity.…”
Section: Pyrrolidine Vs Dimethylamino: Amine-substituted Pyridines In Mncatalyzed Benzylic Oxidationmentioning
confidence: 98%
“…Based on these observations, we concluded that the electronic nature of the ligand is a key factor in controlling the chemoselectivity of these Mn-catalyzed C-H oxidations. 73 In addition, Bryliakov and coworkers have recently developed several electron-rich aminopyridine ligands based on para-substituted aminopyridines (NEt 2 , NMe i Pr, N(CH 2 ) 4 substituents). Particularly, they have shown that the corresponding diferric complexes supported by these ligands can generate high-spin oxoiron(V) intermediates upon reaction with H 2 O 2 , which are active in asymmetric epoxidation and aliphatic hydroxylation reactions.…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 99%
“…Interestingly, the complexes with bulky substituents ( 7c , 8c , 9b , 10b ) promoted ring hydroxylation rather than aliphatic C–H oxidation on the aromatic rings. The complexes with less bulky electron-donating substituents ( 6b , 7b ) such as methoxide facilitated aliphatic C–H oxidation rather than ring hydroxylation . Moreover, it was found that the complexes ( 7 – 10 ) of planar N4 ligands exhibited better performance toward ring hydroxylation when compared to complex 11 , having a tripodal N4 ligand.…”
Section: Homogeneous Transition Metal Complexes In Benzene Hydroxylationmentioning
confidence: 99%
“…The better chelating ability of the tripodal ligand possibly enhanced the electron density on the metal center, leading to lower catalytic selectivity. Furthermore, reaction conditions such as the use of fluorinated alcohols (trifluoroethanol (TFE) and 1,1,1,3,3,3-hexafluoro-2-propanol (HFIP)) instead of acetonitrile and the addition of halogenated carboxylic acid also enhanced the yield and selectivity . The selectivity enhancement in fluorinated solvents is ascribed to their hydrogen donor ability to decrease the nucleophilicity of produced phenol and thereby promote product removal from the active site.…”
Section: Homogeneous Transition Metal Complexes In Benzene Hydroxylationmentioning
confidence: 99%
“…A similar effect was recently observed in aromatic C-H oxidation by a manganese catalyst. 26 An oxidant is another important character in the reaction. The H 2 O 2 /CH 3 CO 2 H oxidative system, which has shown high efficiency in C-H oxidation reactions in other nonheme iron catalytic systems, [27][28][29] gave only minimal conversion (Table 1, entry 6).…”
mentioning
confidence: 99%